Teaching Mathematics in Elementary School using Ethnomathematics of Malind-Papua Tribe Approach - Fredy, Fredy; Sormin, Salman Alparis; Bito, Gregorius Sebo (Universitas Pahlawan Tuanku Tambusai, 2021)
One of the largest tribes in the southern region of Papua is the Malind tribe. They have a number system that can be a link for understanding formal mathematical concepts. This study aims to explore the indigenous number of the Malind tribe, then make patterns in terms of language, identify basic numbers and their use in mathematics learning in elementary schools, especially the concept of addition. The research method used is qualitative. The subjects researched are the men of the traditional, village chief and the people Malind tribe. Data were collected using observation, interviews, and literature study techniques. The results showed that the numeric of the Malind tribe used the base numbers one (hyakod), two (inah), and five (laghr sangga). Counting numbers one to four uses the base numbers one and two, while to count six (laghr sangga hyakod) and so on uses the base numbers one, two, and five. Number system can be used to teach addition concepts assisted blocks media. By using traditional knowledge, students are expected to be able to understand the concept of mathematics well